A Sextuple Knockout Cell Line System to Study the Differential Roles of CRY, PER, and NR1D in the Transcription-Translation Feedback Loop of the Circadian Clock - Chiou, Yi-Ying; Li, Tzu-Ying; Yang, Yanyan; Sancar, Aziz (Frontiers in Neuroscience, 2020)
The transcription-translation feedback loop (TTFL) is the core mechanism of the circadian rhythm. In mammalian cells, CLOCK-BMAL1 proteins activate the downstream genes by binding on the E-box sequence of the clock-controlled genes. Among these gene products, CRY1, CRY2, PER1, PER2, NR1D1, and NR1D2 can regulate the CLOCK-BMAL1-mediated transcription to form the feedback loop. However, the detailed mechanism of the TTFL is unclear because of the complicate inter-regulation of these proteins. Here, we generated a cell line lacking CRY1, CRY2, PER1, PER2, NR1D1, and NR1D2 (Cry/Per/Nr1d_KO) to study TTFL. We compared the Dbp transcription after serum-shock and dexamethasone-shock between Cry/Per/Nr1d_KO cells and cells expressing endogenous CRY (Per/Nr1d_KO) or NR1D (Cry/Per_KO). Furthermore, we found that CRY1-mediated repression of Dbp could persist more than 24 hours in the absence of other proteins in the negative limb of the TTFL. Our Cry/Per/Nr1d_KO cells is suitable system for the studying of differential roles of CRY, PER, and NR1D in the TTFL.